Phenomenology and the unity of consciousness. - Peebles, Graham (Synthese, 2021)
The phenomenology of the unity of consciousness can be analyzed in terms of perceptual spatial and object unity. Subject unity—what we commonly understand by "the unity of consciousness"—has no attendant phenomenology. The further, non-phenomenological, effects of unity can be analyzed in terms of the functional notion of access unity. The unity of consciousness in general can therefore be analyzed in terms of access unity. As a consequence, we can avoid the theoretical introduction of problematic notions such as subsumptive or phenomenal unity.